Sensors for the detection and quantification of bacterial contamination in water for human use - Queirós, Raquel Barbosa (2013)
The deterioration of water quality by Cyanobacteria cause outbreaks and epidemics associated with harmful diseases in Humans and animals because of the toxins that they release. Microcystin-LR is one of the hepatotoxins most widely studied and the World Health Organization, recommend a maximum value of 1mgL 1 in drinking water. Highly specific recognition molecules, such as molecular imprinted polymers are developed to quantify microcystins in waters for human use and shown to be of great potential in the analysis of these kinds of samples. The obtained results were auspicious, the detection limit found, 1.5mgL 1, being of the same order of magnitude as the guideline limit recommended by the WHO. This technology is very promising because the sensors are stable and specific, and the technology is inexpensive and allows for rapid on-site monitoring.